2016
DOI: 10.1007/s00701-016-2844-y
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal ideation, depression, and health-related quality of life in patients with benign and malignant brain tumors: a prospective observational study in 83 patients

Abstract: Patients with intracranial tumors suffer from decreased HRQoL and SI regardless of histopathology. SI is associated with higher BDI scores, but not evident depression (BDI ≥ 18). Thus, patients should be screened specifically and regularly. Lower HRQoL and greatest prevalence of SI at 6 months may help clinicians to find the right time for careful monitoring of patients at risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 44 publications
(78 reference statements)
1
26
0
Order By: Relevance
“…The average percentage of men in the total sample was 51.3%. 17 studies assessed for depression or depressive symptoms using Hospital Anxiety and Depression Scale (HADS-D) [ 4 , 7 , 13 , 14 , 21 , 33 , 35 , 39 43 , 45 , 46 , 49 51 ], 6 used Beck Depression Inventory (BDI) [ 5 , 6 , 23 , 44 , 52 , 54 , 57 ], 2 used the Zung Self-Rating Depression Scale (Zung SDS) [ 51 , 58 ], 2 used Diagnostic and Statistical Manual of Mental Disorders, 4th. Edition (DSM-IV) [ 12 , 47 ], 10 used other methods [ 19 , 20 , 22 , 24 , 34 , 36 , 37 , 48 , 53 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The average percentage of men in the total sample was 51.3%. 17 studies assessed for depression or depressive symptoms using Hospital Anxiety and Depression Scale (HADS-D) [ 4 , 7 , 13 , 14 , 21 , 33 , 35 , 39 43 , 45 , 46 , 49 51 ], 6 used Beck Depression Inventory (BDI) [ 5 , 6 , 23 , 44 , 52 , 54 , 57 ], 2 used the Zung Self-Rating Depression Scale (Zung SDS) [ 51 , 58 ], 2 used Diagnostic and Statistical Manual of Mental Disorders, 4th. Edition (DSM-IV) [ 12 , 47 ], 10 used other methods [ 19 , 20 , 22 , 24 , 34 , 36 , 37 , 48 , 53 , 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…6 studies were excluded because they are in lack of available raw data on prevalence of depression or their main focus is not on the outcome and effect of depression or depressive symptoms [ 39 , 50 , 52 , 53 , 55 , 70 ]. After analyzing the remaining 6 longitudinal studies [ 6 , 7 , 20 , 40 , 51 , 54 ], brain tumor patients presented with a slightly higher prevalence of depression in the follow-up period (Relative Increase Ratio:1.35, 95% CI(1.04, 1.76)) (P = 0.025) (Table 3 ). Sensitivity analysis for the secondary analysis revealed that Angelo’s study has substantial influence on the final result [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, employment status was found to be significantly associated with functional status. A follow-up study conducted by Hickmann et al 32 reported a parallel trend of unemployment as the functional status declines. Though none of the studies have reported any definite association between unemployment and reduced functional status among similar populations, trends and figures explained by previous studies, as well as common sense, support this relationship, especially in countries without unemployment benefits or without adequate labour laws safeguarding employee rights during illnesses.…”
Section: Discussionmentioning
confidence: 97%
“…Brain tumours may be accompanied by a number of comorbidities. While brain tumours may directly affect patients’ cognition, mobility, communication, perception and other neurological functions, these comorbidities may also greatly affect patients’ quality of life 2 8–10. Among these comorbidities, depression is the most common 2 8.…”
Section: Discussionmentioning
confidence: 99%